A symbiotic dessert composed of yam (Dioscorea sp.) and Ubá mango pulp (Mangifera indica L.). (November 2020) - de Almeida Costa, Nataly; de Almeida Paula, Daniele; Brêda, Juliana Dias; Rufino Vieira, Érica Nascif; Furtado Martins, Eliane Maurício; Ramos, Afonso Mota
Abstract: The application of probiotics in dairy products is widely implemented by industries, however, the number of individuals with dietary restrictions is increasing. Thus, there is a growing interest in the development of non-dairy probiotic products. Fruits, tubers, and combinations, offer ample possibilities for the development of functional foods. In this study, a new symbiotic dessert alternative was developed, consisting of yam and Ubá mango pulp. The control dessert (CD), with fiber (DF), with probiotic (DP) and with probiotic and fiber (DPF) were evaluated, during 16 days of storage at 5 °C. The content of β-carotene in desserts varied around 4 mg in 100 g of sample and the total dietary fiber was 8.52 g and 6.53 g in 100 g of the DPF and DP, respectively. The desserts showed a pseudoplastic fluid behavior with initial stress. Average scores greater than 7 ("moderately liked") were attributed from the sensory analysis. The viability of L. plantarum was greater than 8 log CFU/g. Besides, L. plantarum resisted the gastrointestinal conditions simulated in vitro and maintained the counts above 8 Log CFU/g. Thus, the dessert developed is an excelent matrix for addition of probiotic microorganisms, becoming a new functional food alternative. Highlights: Development of a new symbiotic dessert composed of yam and Ubá mango pulp. The dessert is an excellent matrix to convey Lactobacillus plantarum. Probiotic viability after the simulated GIT exceeded 8 Log CFU/100 g. The desserts met the recommendation of dietary fiber in the 100 g product portion. The developed dessert represents an alternative to meet market demands.